Influence of the electronic state of the metals in Cu–Pt/SiO2 catalysts on the catalytic properties in selective hydrogenation of the C≡C bond. Issue 12 (19th September 2021) - Shesterkina, Anastasiya; Shuvalova, Elena; Strekalova, Anna; Tkachenko, Olga; Kustov, Leonid
Abstract: BACKGROUND: The development of highly efficient and selective bimetallic catalytic systems for the hydrogenation of unsaturated compounds is an important scientific task. RESULTS: A new bimetallic 1%Cu‐1%Pt/SiO2 catalyst for the selective hydrogenation of phenylacetylene was developed. The bimetallic catalysts were prepared by a consecutive incipient wetness impregnation method and a redox method with preadsorbed hydrogen. We showed that the catalytic properties of 1%Cu‐1%Pt/SiO2 catalysts and selectivity toward styrene depend on the states of metals and interactions between Cu and Pt in bimetallic particles. The strong contact interaction between Pt 0, Pt δ– and Cu <2+ in sample prepared by the impregnation method provides a high selectivity of about 82% in styrene formation, while the interaction between PtO and CuO phases provides a 60% selectivity under mild conditions. CONCLUSIONS: A new highly effective bimetallic Cu‐Pt/SiO2 catalyst was found for the selective hydrogenation of phenylacetylene with the formation of styrene. © 2021 Society of Chemical Industry (SCI).